(untitled) (Journal of Foreign Language Studies, 2024)
Temporal nouns are a crucial component of both Chinese and Vietnamese. This study conducts a contrastive analysis of the grammatical features of temporal nouns in these two languages, based on the three-dimensional framework of Chinese grammar studies, to identify their similarities and differences. The findings reveal that while temporal nouns in Chinese and Vietnamese share a basic ability to combine with other words, there are minor differences in their syntactic distribution. This research aims to contribute to the teaching and learning of Chinese as a foreign language and to Chinese-Vietnamese translation practices.